2020
DOI: 10.1007/s40121-020-00332-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Evaluation of Early, Low-Dose, Short-Term Corticosteroids in Adults Hospitalized with Non-Severe COVID-19 Pneumonia: A Retrospective Cohort Study

Abstract: Objectives: This study aimed to observe the efficacy of corticosteroids in non-severe COVID-19 pneumonia. Methods: A retrospective study based on propensity score matching was designed to explore the effects of corticosteroids. Primary outcomes included the rate of patients who developed severe disease and mortality. Secondary outcomes included duration of fever, virus clearance time, length of hospital stay, and the use of antibiotics. Results: A total of 475 patients with non-severe COVID-19 pneumonia were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 22 publications
2
74
0
1
Order By: Relevance
“…We found some additional evidence to support the WHO recommendations that corticosteroid treatment is not recommended for mild or moderate patients with COVID-19 in terms of mortality and other clinical outcomes [15][16][17] . As for severe cases requiring oxygen without mechanical ventilation (severe but noncritical), no evidence was found besides the results of the RECOVERY trial 14,18 .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…We found some additional evidence to support the WHO recommendations that corticosteroid treatment is not recommended for mild or moderate patients with COVID-19 in terms of mortality and other clinical outcomes [15][16][17] . As for severe cases requiring oxygen without mechanical ventilation (severe but noncritical), no evidence was found besides the results of the RECOVERY trial 14,18 .…”
Section: Discussionmentioning
confidence: 52%
“…The effect of corticosteroid treatment on other clinical outcomes. One RCT, the RECOVERY trial, and four controlled observational studies using PSM (368 mild or moderate cases 16 and 607 moderate cases 15,17 , as defined by the CNHC, and 70 patients not requiring mechanical ventilation on admission and requiring more than 3 L/min of oxygen during hospitalization to reach saturation above 93%) 18 assessed the Table 4. The RECOVERY trial demonstrated that the number of patients who progressed to invasive mechanical ventilation in the dexamethasone group was significantly lower than that in the usual care group 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on positive results, dexamethasone has been authorized by the UK government for the treatment of critically ill COVID-19 patients (53). However, the comorbidity factors (especially diabetes) should be considered before treatment because some researchers reported that dexamethasone increases the risk of COVID-19 progression to severe disease, especially in patients with diabetes (54,55).…”
Section: Modern Treatmentmentioning
confidence: 99%
“…Antimicrobial therapy was more remarkable in the corticosteroid group. So worse outcomes are expected from corticosteroid therapy in non-severe COVID-19 pneumonia ( Li et al, 2020 ).…”
Section: Corticosteroidsmentioning
confidence: 99%